The Poplar-Poplar Rust Interaction: Insights from Genomics and Transcriptomics. (26th October 2011) - Hacquard, Stéphane; Petre, Benjamin; Frey, Pascal; Hecker, Arnaud; Rouhier, Nicolas; Duplessis, Sébastien
Abstract : Poplars are extensively cultivated worldwide, and their susceptibility to the leaf rust fungus Melampsora larici-populina leads to considerable damages in plantations. Despite a good knowledge of the poplar rust life cycle, and particularly the epidemics on poplar, the perennial status of the plant host and the obligate biotrophic lifestyle of the rust fungus are bottlenecks for molecular investigations. Following the completion of both M. larici-populina and Populus trichocarpa genome sequences, gene families involved in poplar resistance or in rust fungus virulence were investigated, allowing the identification of key genetic determinants likely controlling the outcome of the interaction. Specific expansions of resistance and defense-related genes in poplar indicate probable innovations in perennial species in relation with host-pathogen interactions. The genome of M. Larici-populina contains a strikingly high number of genes encoding small secreted proteins (SSPs) representing hundreds of candidate effectors. Transcriptome analyses of interacting partners in compatible and incompatible interactions revealed conserved set of genes involved in poplar defense reactions as well as timely regulated expression of SSP transcripts during host tissues colonisation. Ongoing functional studies of selected candidate effectors will be achieved mainly on the basis of recombinant protein purification and subsequent characterisation.